À l’écoute des adaptations de Madame Bovary - Mary Donaldson-Evans (Flaubert: Revue Critique et Génétique)
Madame Bovary is a noisy novel. From the laughter of the school children to the blind man’s song, Flaubert constantly appeals to the sense of hearing. Whether it be the ringing of church bells, the continuous humming of Binet’s lathe or the lowing of cattle (to mention only a few of the numerous sounds evoked in the novel), the music of daily life in the provinces is an integral part of the narration.  Theoretically, there is nothing easier for the filmmaker than to reproduce on the screen this sonorous mimicry of the realist text. However, an analysis of the soundtrack of various adaptations reveals an often original interpretation of the text. The resources of the sound effects library as well as the exploitation of certain techniques associated with the soundtrack (voiceover, diegetic and extra-diegetic music, etc.) allow filmmakers to put their own stamp on their adaptations.